Presence, Sources and Transport of Polycyclic Aromatic Hydrocarbons in the Arctic Ocean. Issue 1 (8th January 2023) - Zhang, Lihong; Ma, Yuxin; Vojta, Simon; Morales‐McDevitt, Maya; Hoppmann, Mario; Soltwedel, Thomas; Kirk, Jane; De Silva, Amila; Muir, Derek; Lohmann, Rainer
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are continuously released from multiple sources and are prone to long‐range transport. Little is known regarding their presence, transport and fate in remote and deep oceans. Polyethylene passive samplers were hence deployed at deep moorings and surface seawater in the Fram Strait and Canadian Archipelago, as well as in air and surface water of the lower Great Lakes, a potential high‐emission region, to understand the transport of PAHs to the Arctic. Dissolved PAHs showed significantly higher concentrations in the lower Great Lakes than those in the high Arctic. Concentrations of dissolved PAHs (Σ19 PAHs) ranged from 33 to 300 pg/L in the Fram Strait; the vertical profiles generally exhibited a decreasing trend toward deep waters, which was potentially influenced by hydrological and biogeochemical processes. PAHs were exported from the Arctic Ocean to the North Atlantic through the Fram Strait and the Davis Strait. Plain Language Summary: Polycyclic aromatic hydrocarbons (PAHs) are continuously released from multiple sources, mainly from combustion processes situated in populated and industrial regions. They are capable of long‐distance transport to reach remote and deep oceans. To better understand PAH transport and fate, polyethylene passive samplers were deployed in deep waters of the Fram Strait, surface seawater of the Canadian Archipelago, as well as in air and surface water of the mid‐latitude Great Lakes. Concentrations of dissolved PAHs in the lower Great Lakes were significantly higher than those in the high Arctic, indicating the presence of emission sources in the Great Lakes. The vertical profiles of dissolved PAHs generally exhibited a "surface enrichment and depth depletion" pattern in the Fram Strait, which was potentially affected by hydrological and biogeochemical processes. Pyrogenic sources were the dominant origin of PAHs in both the Arctic and Great Lakes, with some biomass burning sources possibly from wild fires in the sub‐Arctic boreal forest regions. PAHs were exported from the Arctic Ocean to the North Atlantic, with small fluctuations of mass transport through the Fram Strait due to the continuous release of contaminants in mid‐low latitude regions, as well as those primary and secondary sources within the Arctic. Key Points: Polycyclic aromatic hydrocarbons (PAHs) generally exhibited a surface enrichment and depth depletion pattern throughout the water in the Fram Strait PAHs are released from the Arctic Ocean to the North Atlantic through the deep‐water passage Fram Strait and surface pathway Davis Strait PAHs in the Arctic and Great Lake regions were mainly derived from pyrogenic sources, with the existence of some biomass burning sources